PENENTUAN KESERAGAMAN RESPON DAN FAKTOR KOREKSI TLD – 100 (LiF:Mg,Ti) TERHADAP RADIASI SINAR-X - Syaphira Faza Nurulita; Wahyu Setia Budi; Eko Hidayanto; Nunung Nuraeni (BERKALA FISIKA, 2023)
One of the body tissues of radiation workers that is very sensitive to exposure to X-ray radiation is the eye lens. Damage experienced by the lens of the eye exposed to X-ray radiation can develop until blindness occurs due to cataracts. The use of a Thermoluminescence Dosemeter (TLD) can control the external radiation dose received by the eyepiece of radiation workers. In this study there are several objectives, namely to determine the uniformity of the response to TLD-100 (LiF:Mg,Ti) to determine the characteristics of TLD-100 (Lif:Mg,Ti) which is used to measure the radiation dose of the eye lens and determine the TLD-100 correction factor on X-ray radiation to obtain an accurate dose of TLD-100 readings in the eyepiece. The determination of the uniformity of reading response and correction factor of TLD-100 (LiF:Mg,Ti) was carried out on the surface of the water phantom using conventional X-ray radiation sources with variations in voltage (60;70;80) kV at a distance of 100 cm and a wide field. used is 26 x 26 cm. From the results obtained for determining the uniformity of the response of TLD-100 at voltage (60;70;80) kV using Statistical Process Control (SPC) analysis it can be concluded that TLD-100 has a uniform response because it is between the Lower Warning Limit (LWL) and Upper Warning Limit (UWL). However, according to ISO 21909 at a voltage of 60 kV it is necessary to re- illuminate because the response variation value obtained is 40.95% exceeding the specified response variation value limit which is not more than 20% while at a voltage of 70 kV with a response value of 20.05% and 80 kV with a response variation value of 13.93% did not exceed the predetermined limits while the results of determining the TLD-100 correction factor (LiF:Mg,Ti) for each voltage decreased in the range of 0.753 to 0.576. The correction factor at a voltage of 60 kV to 80 kV does not reach the ideal correction factor because the voltage used for calibration uses low energy while the calibration used is for calibration at high voltages.